2012
DOI: 10.1128/jb.05740-11
|View full text |Cite
|
Sign up to set email alerts
|

Cj1386 Is an Ankyrin-Containing Protein Involved in Heme Trafficking to Catalase in Campylobacter jejuni

Abstract: Campylobacter jejuni, a microaerophilic bacterium, is the most frequent cause of human bacterial gastroenteritis. C. jejuni is exposed to harmful reactive oxygen species (ROS) produced during its own normal metabolic processes and during infection from the host immune system and from host intestinal microbiota. These ROS will damage DNA and proteins and cause peroxidation of lipids. Consequently, identifying ROS defense mechanisms is important for understanding how Campylobacter survives this environmental str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…4C). Indeed, the sensitivity of the ⌬cj1386ϩcj1386 Y57A strain also was similar to that of the ⌬katA mutant strain (25.30 mm [7]; not significant at P Ͼ 0.05). This result highlights that loss of tyrosine 57 results in a severe inability of C. jejuni to resist H 2 O 2 at levels comparable to those in the absence of the catalase enzyme itself.…”
Section: Figmentioning
confidence: 68%
See 3 more Smart Citations
“…4C). Indeed, the sensitivity of the ⌬cj1386ϩcj1386 Y57A strain also was similar to that of the ⌬katA mutant strain (25.30 mm [7]; not significant at P Ͼ 0.05). This result highlights that loss of tyrosine 57 results in a severe inability of C. jejuni to resist H 2 O 2 at levels comparable to those in the absence of the catalase enzyme itself.…”
Section: Figmentioning
confidence: 68%
“…Specifically, KatA immunoprecipitated from a ⌬cj1386 mutant had a significant reduction in the hemin content associated with its KatA relative to KatA isolated from the wild-type strain. In turn, the decreased hemin content of KatA in the ⌬cj1386 mutant resulted in reduced catalase activity within the cell and, consequently, sensitivity to H 2 O 2 (7). In this report, we further characterize Cj1386 function to demonstrate its direct role in hemin trafficking within C. jejuni.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The upregulation of the tpx, katA and ahpC transcripts coincided with a peak in neutrophil numbers in the chamber indicating the importance of these genes for oxidant detoxification in vivo. Furthermore, both katA and ahpC mutants exhibited a reduced ability to colonize the chick caecum compared to the wild-type strain (Palyada et al, 2009), and the katA mutant was recently shown to be outcompeted by the wild-type strain in the piglet infectious model (Flint et al, 2012) Other upregulated or downregulated genes Transcriptome analysis of the cj1000 : : aph mutant revealed upregulation of genes involved in flagellum biogenesis (flaA, flaB, flgG2, flgH, fliD and fliS), the exceptions being flaC and flhB, which were downregulated (Table 1). Despite these changes in transcript levels, the motility in vitro of the cj1000 mutant is unchanged compared to the wild-type strain (data not shown).…”
Section: Oxidative Stress Defencesmentioning
confidence: 99%